Elevated urinary sVCAM-1, IL6, sIL6R and TNFR1 concentrations indicate acute kidney transplant rejection in the first 2 weeks after transplantation - Reinhold, Stephan; Krüger, Bernd; Krämer, Bernhard (Cytokine, 2012)
We tested the hypothesis that increased urinary cytokine concentrations may indicate an acute kidney transplant rejection. Eight patients with an early rejection in their protocol biopsy about 14days after transplantation (group A), 9 patients with a biopsy proven rejection 2-3months after transplantation (group B) and 18 patients without acute rejection in their protocol biopsies both at 14days and 3months (group C, represents the control group) were chosen for this study. At the time of biopsy, the mean urinary concentration of interleukin 6 (IL6), soluble IL6 receptor (sIL6R), tumor necrosis factor receptor 1 (TNFR1), and soluble vascular cell adhesion molecule −1 (sVCAM-1) were significantly higher in patients with an early acute transplant rejection, i.e. in group A compared to patients in the control group (p<0.01). Additionally we found already 14days after transplantation significantly higher concentrations of urinary sIL6R and sVCAM-1 in group B patients who suffered of late acute rejection compared to patients with no acute rejection (group C, p<0.05). No significant correlation could be shown for interleukin 1 receptor antagonist (IL1ra), TNF, and TNFR2. In conclusion, elevated urinary concentrations of IL6, sIL6R, TNFR1 and sVCAM-1 clearly indicate an early acute transplant rejection. Especially sVCAM-1 may also serve as an early marker of an upcoming late rejection. However, further studies are warranted to verify the value of individual cytokine profiles to predict acute rejection episodes.
Available online 30 December
Gesehen am 06.06.2018